1995
DOI: 10.1111/j.1365-277x.1995.tb00308.x
|View full text |Cite
|
Sign up to set email alerts
|

Management of patients with food intolerance in irritable bowel syndrome: the development and use of an exclusion diet

Abstract: Food intolerance is an important cause of abdominal symptoms. As no objective tests are available to identify the foods concerned, diets are essential for the management of these patients. The fewer foods allowed in the diet, the greater is the chance of success. Our original studies of 182 patients between 1979 and 1982, using a diet of lamb, rice and pears, had resulted in a 67% success rate. The foods most commonly involved were wheat (6O%), cows' milk (44%) and corn (44%). A less restrictive exclusion diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 7 publications
1
47
0
1
Order By: Relevance
“…It has no diagnostic markers but symptoms include excessive¯atus, bloating and variable bowel habit (Parker et al 1995). The aetiology of IBS is unknown although it has been suggested that the gut micro¯ora have a role in development.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…It has no diagnostic markers but symptoms include excessive¯atus, bloating and variable bowel habit (Parker et al 1995). The aetiology of IBS is unknown although it has been suggested that the gut micro¯ora have a role in development.…”
Section: Irritable Bowel Syndromementioning
confidence: 99%
“…More than 50% of patients with CD reacted positively to such diets, suggesting that microbial fermentation in the gut is a factor in the pathogenesis of the disease (Parker et al 1995).…”
Section: In¯ammatory Bowel Diseasementioning
confidence: 99%
“…Long-term follow-up of the flora of IBS patients suggests that the flora is unstable, with alteration in the rank order of species (10) in contrast to healthy individuals (11a). Many IBS patients report exacerbation of symptoms by specific foods, and restrictive diets avoiding such foods may lead to improvement of their symptoms (12)(13)(14). Exposure to intolerant foods results in changes in the gut flora and an increase in bacterial metabolic activity as demonstrated by increased production of short-chain fatty acids (15).…”
mentioning
confidence: 99%
“…O gastroenterologista deve explicar as implicações deste diagnóstico ao paciente e, assim, assegurar-lhe que não foi encontrada nenhuma doença estrutural e que, em alguns casos, há eventualmente uma melhora espontânea (49) . Deve ser oferecida orientação sobre a redução de elementos potencialmente laxativos na dieta (por exemplo, cereais e certas frutas contendo frutose e oligossacarídeos) (50) e redução na ingestão de álcool. Abster-se de produtos lácteos pode ajudar, se forem consumidos mais de 240 mL de leite ou o seu equivalente por dia (41) .…”
Section: Figura 2 Diarreia Crônica Sem Dorunclassified